2021
DOI: 10.3390/ijerph182312834
|View full text |Cite
|
Sign up to set email alerts
|

How Power Influences Decision-Makers’ Investment Behavior in the Domains of Loss and Gain

Abstract: We present a study (N = 645) investigating how power alters people’s propensity to take investment risks in a changing decision context of gains and losses and the intensity of their reactions to this experience. The results indicate that people in a state of power made more risky investment decisions than the control group regardless of prior gain or loss outcome, whereas people lacking power took less investment risk than the control group, regardless of previous outcomes. Moreover, people with power and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…We observed a positive relationship between power and focus on rewards versus threats, which aligns with the studies conducted, for example, by Anderson and Berdahl (2002), Inesi (2010), and Whitson et al (2013). Additionally, we found a significant and positive correlation between power and risky financial choices, which supports earlier research conducted by Galinsky et al (2014), Sekścińska, Rudzinska‐Wojciechowska, and Jaworska (2022), Sekścińska, Rudzinska‐Wojciechowska, and Kusev (2022), and Sekścińska and Rudzinska‐Wojciechowska (2021). We also replicated the previously demonstrated negative association between power and the perception of financial risk, as shown by Kim and McGill (2011).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed a positive relationship between power and focus on rewards versus threats, which aligns with the studies conducted, for example, by Anderson and Berdahl (2002), Inesi (2010), and Whitson et al (2013). Additionally, we found a significant and positive correlation between power and risky financial choices, which supports earlier research conducted by Galinsky et al (2014), Sekścińska, Rudzinska‐Wojciechowska, and Jaworska (2022), Sekścińska, Rudzinska‐Wojciechowska, and Kusev (2022), and Sekścińska and Rudzinska‐Wojciechowska (2021). We also replicated the previously demonstrated negative association between power and the perception of financial risk, as shown by Kim and McGill (2011).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the effects of state of power and sense of power are usually consistent (e.g., Anderson & Berdahl, 2002; Anderson & Galinsky, 2006; Cote et al, 2011; for a review, see Rucker et al, 2012). However, some studies have found an interaction effect between state of power and sense of power (Chen et al, 2009; Sekścińska & Rudzinska‐Wojciechowska, 2021; Sekścińska, Rudzinska‐Wojciechowska, & Jaworska, 2022; Strelan et al, 2014). For this reason, it is crucial to consider both components of power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between greater levels of power measured with the Sense of Power Scale [ 9 ] and riskier gambling choices has also been observed [ 20 , 21 ]. Similarly, experimentally-induced state of having power results in greater investment risks than low power [ 3 , 20 ].…”
Section: Introductionmentioning
confidence: 99%